Prevalence of Adverse Childhood Experiences (ACEs) in child sex offenders and associations with health indicators - Κωνσταντίνος Τόγκας; Γεώργιος Αλεξιάς (Ψυχολογία: το Περιοδικό της Ελληνικής Ψυχολογικής Εταιρείας, 2024)
This study aimed to evaluate the prevalence of ACEs among child sex offenders in Greece and their associations with specific health indicators (e.g., smoking, alcoholism). A cross-sectional study was conducted (between February and April 2023) using a convenience sample of 158 child sex offenders in Tripolis prison, Greece. The questionnaire included demographic and criminal information, the BRFSS ACEs module, and four additional childhood experiences (death of a parent or sibling, etc.). Their mean age was 50.5 years (min=22, max=83, range=61), and the majority were smokers (62%) and had at least one chronic disease (63.3%). Small percentages used drugs (7.6%) and were alcoholics (8.2%). The mean ACEs score was .76 (min=0, max=6, range=6). One out of three offenders (33.5%) had experienced at least one ACE and 6.3% had four or more ACEs. The most common ACEs were intimate partner violence (15.8%), physical abuse (13.3%), and parental separation/divorce (12.7%). Smaller percentages were recorded for substance abuse and emotional abuse (10.8%), incarcerated household members (10.1%), sexual abuse (7.59%), and mental health problems of household members (0.6%). Those with four or more ACEs had a higher likelihood of being smokers (odds ratio=5.97, 95% CI: 1.074-48.335) and alcoholics (odds ratio=1.37, 95% CI: 1.028-1.124). Age was negatively correlated with the ACEs scores (r=-.312, p<.001). In conclusion, these offenders reported many ACEs, but fewer than those found in other studies abroad. Future research should further examine the preliminary findings of this study.